General vaccination knowledge influences nurses' and midwives' COVID-19 vaccination intention in Cyprus: a nationwide cross-sectional study - Fakonti, Georgia; Kyprianidou, Maria; Iordanou, Stelios; Toumbis, Giannos; Giannakou, Konstantinos (My University, 2022)
This cross-sectional study was conducted during the period between 08 and 28 December 2020 to investigate the association of nurses' and midwives' level of vaccination knowledge and the COVID-19 vaccine acceptance for themselves during the COVID-19 pandemic era in Cyprus. Participants included registered nurses and midwives working in public or private service provision. Data collection was achieved using a self-administered questionnaire with questions on socio-demographic characteristics, questions assessing participants' general vaccination knowledge, and questions related to COVID-19 vaccination. A total of 437 responders answered the survey, with 93% being nurses and 7% midwives. The results indicate that as the vaccination knowledge score increases (higher knowledge) the probability of accepting the COVID-19 vaccination increases too (OR = 1.30, 95% CI: 1.13-1.48). The association between vaccination knowledge and the intention to be vaccinated against COVID-19 remained statistically significant, even after adjusting for age and gender (OR = 1.28, 95% CI: 1.12-1.47), socioeconomic (OR = 1.29, 95% CI: 1.12-1.48), and demographic characteristics (OR = 1.29, 95% CI: 1.11-1.49). Also, as age increases, the probability of accepting the COVID-19 vaccination increases, while female respondents had a lower probability of accepting the COVID-19 vaccination than male respondents. This study demonstrated that COVID-19 vaccination acceptance is related to the vaccination knowledge of the nurses and midwives in Cyprus. Targeted vaccination campaigns are needed to improve nurses' and midwives' level of vaccination knowledge in order to achieve a better coverage among them, as well as to influence their patients' ultimate positive vaccine decision.
Keywords: Midwife; COVID-19; Cyprus; Vaccination; Coronavirus; Knowledge; Nurse; Vaccine